2015
DOI: 10.1590/0103-8478cr20131532
|View full text |Cite
|
Sign up to set email alerts
|

Sorghum cultivars of different purposes silage

Abstract: This study aimed to assess the fermentation profile, losses and chemical composition of the silages of five sorghum cultivars. A completely randomized design with five replicates was used. The experimental treatments were represented by five sorghum cultivars (Sorghum bicolor (L). Moench): 'BRS Ponta Negra' , 'BRS 610', 'BRS 655', 'BRS 800' and 'BRS 810'. There was variation (P<0.05) RESUMO Objetivou-se com este estudo avaliar o perfil fermentativo, perdas e a composição bromatológica de silagens de cinco c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 10 publications
2
11
0
1
Order By: Relevance
“…The WSC of the SM group was increased due to mixing S and M forages, leading to improved LA content (Table 2). The results derived from this study were in agreement with the findings of Kaplan (2013) and Pinho et al (2015), who stated increased level of WSC enhanced the LA content of silage and accounted for a lower pH value. a,b,c Values within a row with different superscripts differ significantly at P<0.05 DM: Dry Matter, g kg -1 ; CP: Crude Protein, g kg -1 DM; Ash, g kg -DM; NDF: Neutral Detergent Fiber, g kg -1 DM; ADF: Acid Detergent Fiber, g kg -1 DM; ADL: Acid Detergent Lignin, g kg -1 DM; Hcell: Hemicellulose, g kg -1 DM; Cell: Cellulose, g kg -1 DM; WSC: Water Soluble Carbohydrate, g kg -1 ; NH3-N: Ammonia Nitrogen, g kg -1 TN; LA: Lactic Acid, g kg Differences with respect to the CP and ash content among the silage groups were found significant (P<0.01).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The WSC of the SM group was increased due to mixing S and M forages, leading to improved LA content (Table 2). The results derived from this study were in agreement with the findings of Kaplan (2013) and Pinho et al (2015), who stated increased level of WSC enhanced the LA content of silage and accounted for a lower pH value. a,b,c Values within a row with different superscripts differ significantly at P<0.05 DM: Dry Matter, g kg -1 ; CP: Crude Protein, g kg -1 DM; Ash, g kg -DM; NDF: Neutral Detergent Fiber, g kg -1 DM; ADF: Acid Detergent Fiber, g kg -1 DM; ADL: Acid Detergent Lignin, g kg -1 DM; Hcell: Hemicellulose, g kg -1 DM; Cell: Cellulose, g kg -1 DM; WSC: Water Soluble Carbohydrate, g kg -1 ; NH3-N: Ammonia Nitrogen, g kg -1 TN; LA: Lactic Acid, g kg Differences with respect to the CP and ash content among the silage groups were found significant (P<0.01).…”
Section: Resultssupporting
confidence: 92%
“…This result was expected because it was stated by some researchers in the earlier studies that the forage quality may strongly be affected by species, genotype, maturity at harvesting period, steam/leaf ratio, number of panicles (Cândido et al, 2002;Da Silva et al, 2012). The results were consistent with an adequate CP level for the functioning of ruminal microbiota (Pinho et al, 2015). Ash referring to mineral content in forages, influenced by maturity, is found higher in seed than those of other parts.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…According to Pinho et al (2015), lower levels for these acids are associated with the rapid acidification of the medium, due to its susceptibility to low pH values.…”
Section: Resultsmentioning
confidence: 99%
“…The bacterial activity that occurs during ensiling decreases as DM content increases (KAISER et al, 2004), which reduces the production of organic acids, such as lactic acid, consequently decreasing the rate of pH reduction. In addition, elevated levels of WSC promote vigorous fermentations within the silo (PINHO et al, 2015). Zhang et al (2015), evaluated the quality of sweet sorghum silages and observed pH values of 4.16 and N-NH 3 of 7.66 % of total N. Regarding silages of sweet sorghum cultivars, the lower DM content observed at the first crop than at the second crop may have been due to higher ethanol production (Table 4).…”
Section: Resultsmentioning
confidence: 99%